Unexpected Diagnosis of Chondroma in a Pediatric Patient Presenting with Tongue Swelling: A Case Report - BHAUMIK, SOMDATTA; Mondal, Rajib Kumar (Tropical Journal of Pathology and Microbiology, 2025)
Chondromas are rare benign cartilaginous tumors, especially uncommon in the oral cavity and even rarer in pediatric patients. We present a case of a 5-year-old male child with a swelling on the dorsum of the tongue, initially diagnosed as an epidermoid cyst based on MRI findings. However, histopathological examination revealed a chondroma, highlighting the importance of histopathological analysis in confirming diagnoses and guiding appropriate management, particularly in atypical cases.